A rare case of 2, 4-Dichlorphenoxyacetic acid (2, 4-D) poisoning - Singla, Sanjay; Malvia, Sunny; Bairwa, Ram Prakash; Asif, Mohammad; Goyal, Suresh (International Journal of Contemporary Pediatrics, 2017)
2,4-D (2,4-dichlorphenoxyacetic acid) is a selective herbicide which kills broad leaved plants but not grasses. It is not toxic to beneficial insects and has moderate mammalian toxicity. It is used widely in agriculture and forestry as an herbicide in either ester or salt formulation. Human poisoning with 2,4- D is rare and is generally following suicidal ingestion. Here we report a case of 2,4- D poisoning.